2012
DOI: 10.1021/cm201602a
|View full text |Cite
|
Sign up to set email alerts
|

Room Temperature Synthesis and Thermal Evolution of Porous Nanocrystalline TiO2 Anatase

Abstract: TiO 2 nanoparticles are a major component in many areas, and especially for dye-sensitized solar cells (DSSC) as a result of their electronic structure that allows them to collect the electrons transferred from the dye molecules after sunlight irradiation, as well as of their semiconducting properties, which provide the surface transport of these electrons up to the collecting electrode. However, for this application or others, the optimization of both structural and electronic properties of titanium oxide is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(38 citation statements)
references
References 63 publications
1
30
0
Order By: Relevance
“…Following the results of Enright, Hegasy was able to follow the evolution of the indirect energy band gap as a function of the anatase crystal size and observed an energy shift of that band Δ Eg(eV) = 0.15 eV. By applying TiO 2 m with the anatase phase to the development of DSSC solar cells, Hegasy and collaborators reported an efficiency η  = 0.68 % [27]. …”
Section: Resultsmentioning
confidence: 94%
“…Following the results of Enright, Hegasy was able to follow the evolution of the indirect energy band gap as a function of the anatase crystal size and observed an energy shift of that band Δ Eg(eV) = 0.15 eV. By applying TiO 2 m with the anatase phase to the development of DSSC solar cells, Hegasy and collaborators reported an efficiency η  = 0.68 % [27]. …”
Section: Resultsmentioning
confidence: 94%
“…Further the synthesis method play significant influence on the values with the wet chemical methods leading to lower E g . Recently Prouzet's [59] group has shown that the indirect bandgap model gives better agreement on the E g values of anatase nanoparticles. Further, Uddin et al's [60] report on the bandgap of TiO 2 show that the indirect bandgap model gives lower E g , close to the reported bulk values (3.2 eV), than the estimates obtained using direct bandgap model.…”
Section: Resultsmentioning
confidence: 99%
“…We use an iron oxide, (α-Fe 2 O 3 ), named haematite (figure 1a), with a band gap of about 2.2 eV, corresponding to a visible wavelength λ Fe 2 O 3 ∼ 560 nm [23] and previously studied in [24,25]. We moreover present a new colloidal particle taking advantage of an alternate photoactive material: titania (TiO 2 ) in the anatase phase (figure 1b), with a bandgap of 3.1 eV, corresponding to the wavelength λ TiO 2 = 400 nm [26]. The particles are conveniently observed with an inverted optical microscope equipped with high magnification objectives, typically 60× or 100× and a conventional brightfield diascopic illumination.…”
Section: Photo-activated Colloids (A) Photocatalytic Materialsmentioning
confidence: 90%